Identification key to the genera of Carabidae (Coleoptera) of the paramos of Ecuador and southern Colombia - MORET, PIERRE (Revista Colombiana de Entomología, 2003)
This paper provides a key for identification of the genera of Carabidae inhabiting the paramos of Ecuador and southern Colombia with illustrations, and their geographic distribution is briefly summarized.